Kampanye Moderasi Beragama di Facebook: Bentuk dan Strategi Pesan (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2019)
This paper seeks to formulate an ideal concept in campaigning for religious moderation in Indonesia through the use of Facebook. There are three things that underlie this study, 1) The mass movement of radicalism in the name of religion in Social Media; 2) Potential conflicts on the basis of SARA; 3) The importance of efforts to strengthen religious moderation in Indonesia based on social media. The idea of religious moderation must be strengthened by the national movement. The library research method (library study) becomes the scientific foundation for exploring various literature, both primary and secondary related to the concept of religious moderation in Indonesia. The results of this study offer a message form and strategy in campaigning for religious moderation on Facebook. First, the form of a religious moderation campaign on Facebook must be ideologically-oriented (oriented towards changing attitudes, behavior and public views). Second, campaign messages must be informative and persuasive (based on data and facts) and can influence other Facebook users to participate in creating campaigns (social campaigns) on religious moderation. A religious moderation campaign message on Facebook does not necessarily have to content writing, it can also be an illustrative (animated) picture or a short educational video.